Assembleia de aves territorialistas na formação espinilho : densidade e seleção de habitat reprodutivo - Pereira, Mauricio da Silveira (2015)
Inserted into the grassland matrix of the pampa biome is Espinal ecoregion with distinctive arboreal components, predominantly located in Argentina with a small insertion in Brazil, more precisely in the most western portion of Rio Grande do Sul. This ecosystem is considered threatened and of high conservation priority in Argentina. In the state of Rio Grande do Sul its remnants are restricted to the Espinilho State Park and its neighboring areas. At the national scope, this region is a household to a bird species group restricted to this ecosystem, and several of them are classified as endangered. Although widespread relevance in the literature on the species and its Espinal habitat relationship we lack studies in the region, especially on population densities and vegetation features selected for these species. Thus, we aimed to answer questions related to density of breeding territory and vegetation features that may be acting in the distribution of the assemblage of territorial birds in Espinal ecosystem in the state. Four different plots (in sizes and characteristics) were selected (total of 206.2 ha) and nine spot-mapping census were carried out in each area during the 2012/2013 breeding season. Birds were color and metal banded previously in the plots to facilitate later identification of territories. Fifty-one species provided data of at least one territory. The territory densities (territory / 100 ha) ranged from 0.09 to 110.96. Common species in state as Zonotrichia capensis, Sicalis flaveola and Troglodytes musculus had higher densities. Five of seven measured variables show statistically difference (Kruskal-Wallis test, P <0.05) between the areas: tree density, tree richness, tree width, herbaceous height and shrubs density. Twenty-one species preferred areas with high coverage of tree layer. Areas with high herbaceous height favored grassland or occupants of shrubby areas, as Volatinia jacarina, Sicalis luteola, Sporophila caerulescens and Euscarthmus meloryphus. Places where other tree species occur, beyond the most characteristic species of Espinal ecosystem (Prosopis spp., Vachelia caven) were used for more edge-forested species such as Elaenia parvirostris, Turdus amaurochalinus, Synallaxis frontalis, Poospiza melanoleuca, Cranioleuca pyrrhophia and Cyanocorax chrysops. Ground foraging species including those of some conservation interest, such as Asthenes baeri, Drymornis bridgesii, Coryphistera alaudina, Pseudoseisura lophotes and Gubernatrix cristata, selected areas with livestock presence with reduced herbaceous height and lower shrubs density. Our data suggest prudence in the cattle removal after the acquisition of new areas of Espinilho State Park, requiring the monitoring of all actions aimed at further any change in vegetation structure. Such changes may reflect negatively on the use of areas for some species.